Biauricular heart wound - Trostchansky, José; Bertullo, Hugo; di Leoni, Francisco; Pomi, Jorge (Cirugía del Uruguay, 1976)
Authors report an observation of a bullet wound caliber 38, that crossed transversely the heart, penetrating by the right aurícula and leaving by the left. It was immediately operated suturing boths wounds . Recovery was normal . The patient operated eight months ago is very well.